2020
DOI: 10.1097/ccm.0000000000004498
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Risk Factors and Mortality From Ischemic and Hemorrhagic Strokes in Patients Receiving Venoarterial Extracorporeal Membrane Oxygenation: Results From the Extracorporeal Life Support Organization Registry

Abstract: Objectives: Although acute brain injury (ABI) is common in patients receiving extracorporeal membrane oxygenation (ECMO), little is known regarding the mechanism and predictors of ischemic and hemorrhagic stroke. We aimed to determine the risk factors and outcomes of each ischemic and hemorrhagic stroke in patients with venoarterial (VA)-ECMO support.Design: Retrospective analysis.Setting: Data reported to the Extracorporeal Life Support Organization by 310 extracorporeal membrane oxygenation centers from 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 40 publications
3
50
1
Order By: Relevance
“…A second prospective single-center analysis identified that hyperoxia (PO 2 > 300 mmHg) during the first hour after resuscitation was associated with a worse neurologic outcome at discharge [75]. A recent analysis of 10,342 VA-ECMO patients from the ELSO showed that all subtypes of ABI were more common in patients with hyperoxia, as measured by 24-hour ABG [76]. However, data on this for ECPR patients are limited.…”
Section: Clinical Research On "Hyperoxia" In Ecprmentioning
confidence: 99%
See 1 more Smart Citation
“…A second prospective single-center analysis identified that hyperoxia (PO 2 > 300 mmHg) during the first hour after resuscitation was associated with a worse neurologic outcome at discharge [75]. A recent analysis of 10,342 VA-ECMO patients from the ELSO showed that all subtypes of ABI were more common in patients with hyperoxia, as measured by 24-hour ABG [76]. However, data on this for ECPR patients are limited.…”
Section: Clinical Research On "Hyperoxia" In Ecprmentioning
confidence: 99%
“…In addition to HIBIs, acute ischemic stroke (AIS) and intracranial hemorrhage (ICH) are major complications that increase mortality in patients supported with ECMO [76,84,85]. In patients treated with VA-ECMO, the prevalence of AIS is 3.3% and may be as high as 16% on autopsy [86,87].…”
Section: Ischemic Stroke and Intracranial Hemorrhage In Va-ecmomentioning
confidence: 99%
“…However, neurologic injuries can occur while on ECMO and can be devastating. The reported incidence of such injuries ranges widely from 1 to 78% with a median of 13% [7][8][9][10]. As utilization of ECMO becomes more mainstream, the overall prevalence of associated neurologic injuries is also expected to increase.…”
Section: Introduction To Extracorporeal Membrane Oxygenationmentioning
confidence: 99%
“…[1][2][3] Patients undergoing extracorporeal membrane oxygenation (ECMO) constitute a special population with a high risk of acute brain injury (ABI), up to 15.1% in patients undergoing veno-arterial (VA) ECMO, and 7.1% in patients undergoing veno-venous ECMO. 4 While evidence for improving neurological outcome with therapeutic hypothermia 32-36°C is well delineated in cardiac arrest, 1,[5][6][7][8][9] the effect of hypothermia in VA-ECMO is unknown. VA-ECMO patients are susceptible to reperfusion injury given their prolonged hypoperfusion preceding full restoration of cerebral blood flow, which may benefit from hypothermia.…”
Section: Introductionmentioning
confidence: 99%